INEFFECTIVENESS OF THE LAW ON CROSS INSOLVENSI UNCITRAL MODEL - Sefriani, Sefriani (Faculty of Law, Universitas Sebelas Maret, 2019)
Legal problems due to cross border insolvency are increasingly complex. The United Nations has issued the 1997 Model Law on Cross border Insolvency (CBI) to help countries solve their CBI problems. However, this model law is not effective because very few countries adopted it. The legal problem studied is why very few countries adopted the model law and how to overcome the ineffectiveness of the model law. The results of the study indicate that the lack of adoption of the model law caused by: the model law is only a non-binding legislative text; Too much flexibility encourages deviations from the provisions; do not want to reduce their sovereignty, status quo, international cooperation recommended by the model law is not always of primary interest, and many countries have been bound by international agreements on regional CBI which are considered more relevant than the model law. The solutions that can be suggested to overcome the ineffectiveness of the model law on CBI are national bankruptcy laws mechanism; the International Treaties and Conventions mechanism; Rules, Regulations, Principles and Guidelines mechanisms and protocol or adhoc agreements.